Violence towards nurses and factors affecting violence in hospital settings: an Italian cross-sectional study - Luciani, Michela; Spedale, Valentina; Romanenghi, Monica; Villa, Candida Ester; Ausili, Davide; Di Mauro, Stefania (La Medicina del Lavoro, 2016)
Violence towards nurses is a widespread phenomenon in Italy about which statistics are lacking. Aim: To investigate the prevalence of violence towards nurses in a health care structure in the north of Italy. Method: An observational cross-sectional study. Data were collected anonymously with a questionnaire developed by Zampieron et al. (2010) on a stratified sample of 198 nurses working in a major Italian Hospital in the Lombardy Region. Results: 43% of the sample (n=85/198) experienced violence in the previous twelve months with a mean of 4 aggressions each. Aggressors were mainly patients (53.3%) or relatives (26.7%), men (63.1%) aged between 36 and 50 years (27.9%). Of the verbal aggressions, one out of four was by a colleague or a superior. The emotional, physical and professional consequences were serious and the result of both physical and verbal violence. Nevertheless, among those who experienced aggressions, 57% did not ask for help and of those who did (43.0%) about 75% asked for help and support from their colleagues. Conclusions: Violence toward nurses exists and it is commonplace in the workplaces studied, even in the horizontal form. It is important to implement assessment and risk prevention and management measures, via specific training of nurses, and offer support for the victims and an anonymous formal report system guaranteed by the authorities.